ProgTest: An environment for the submission and evaluation of programming assignments based on testing activities - de Souza, Draylson Micael; Maldonado, J C; Barbosa, E F (2011 24th IEEE-CS Conference on Software Engineering Education and Training (CSEE&T), 2011)
Programming foundations is not an easy subject to be taught - many students have difficulties understanding the abstract concepts of programming and have a wrong view about the programming activity. In order to address these problems, experiences have suggested the integrated teaching of programming concepts and software testing in introductory CS courses. Shortly, the idea is that testing can contribute to enhance the students' capabilities of understanding and analysis. However, such perspective requires tools to provide an adequate feedback to evaluate the students' performance concerning programming and testing activities. In this paper we describe ProgTest - a web-based tool for the submission and automatic evaluation of practical programming assignments based on testing activities. Results from a preliminary validation of ProgTest are also presented. Such results provide evidences on the practical use of ProgTest as a supporting mechanism for the integrated teaching of programming foundations and software testing.